التحليـل الإحصـائي لتجارب القطـع المنشقة المنشقة - خلف كمال علوان; نايف قتيبة نبيل (Journal of Economics and Administrative Sciences, 2008)
This research aims to employ a method by use the formulas that determine the degrees of freedom for each component of sources of variation to calculate the sums of squares for each component as a fast and accurate method compared with another methods in Split – split plots experiment